2014
DOI: 10.1501/vetfak_0000002602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of brush cytology (cytospin technique) and cultural results in the diagnosis of keratoconjunctivitis in a goat herd

Abstract: Summary:In this study, cytological examination of smears prepared with cytospin and bacteriological isolation from the samples taken with cytobrush from corneal surface of goats with keratoconjunctivitis were evaluated. An outbreak of infectious keratoconjunctivitis, which is particularly affecting kids, was determined in a herd of Saanen goats consisting of 200 animals (120 kids and 80 goats) that located in Bursa province between 2011 and 2012. One hundred and twenty kids were affected severely in this occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
2
0
1
Order By: Relevance
“…In the present study, based on strong TNFα, IL-1β, IL-6, IL-4 and MMP-9 immunopositivity having been detected in the in ammatory cells, it was considered that the indicated cytokines and enzyme could have accompanied the development of the granuloma in the eye diagnosed with mixed bacterial infection. The microorganisms isolated from the eyes of a Gentoo penguin chick in the present study differ from those reported to have been isolated from the eyes of mammals and exotic birds in previous studies ( Silvanose et al 2001;Cullen, 2003;Bonelli et al 2014;Cakir et al 2014;Sala et al 2016). Furthermore, the microorganisms isolated in the present study have been determined to differ from the bacteria reported to have been detected in freshwater samples from the same location (Jara et al 2020).…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…In the present study, based on strong TNFα, IL-1β, IL-6, IL-4 and MMP-9 immunopositivity having been detected in the in ammatory cells, it was considered that the indicated cytokines and enzyme could have accompanied the development of the granuloma in the eye diagnosed with mixed bacterial infection. The microorganisms isolated from the eyes of a Gentoo penguin chick in the present study differ from those reported to have been isolated from the eyes of mammals and exotic birds in previous studies ( Silvanose et al 2001;Cullen, 2003;Bonelli et al 2014;Cakir et al 2014;Sala et al 2016). Furthermore, the microorganisms isolated in the present study have been determined to differ from the bacteria reported to have been detected in freshwater samples from the same location (Jara et al 2020).…”
Section: Discussioncontrasting
confidence: 98%
“…S7). In agreement with the ndings of previous reports for cytospin slides prepared from samples of animals with keratoconjunctivitis (Cakir et al 2014), the present study revealed the presence of binucleated epithelial cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation